1998
DOI: 10.1126/science.281.5375.375
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Treponema pallidum , the Syphilis Spirochete

Abstract: The complete genome sequence of Treponema pallidum was determined and shown to be 1,138,006 base pairs containing 1041 predicted coding sequences (open reading frames). Systems for DNA replication, transcription, translation, and repair are intact, but catabolic and biosynthetic activities are minimized. The number of identifiable transporters is small, and no phosphoenolpyruvate:phosphotransferase carbohydrate transporters were found. Potential virulence factors include a family of 12 potential membrane prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
999
3
27

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 990 publications
(1,059 citation statements)
references
References 75 publications
30
999
3
27
Order By: Relevance
“…Moreover, it has been shown that Dv superoxide reductase can be the final electron acceptor of a NADPH/NADPH oxidoreductase/rubredoxin electron transfer chain in vitro [20,21]. In Tp, analysis of the full genome shows the presence of homologues for the additional constituents of a primitive SOR-dependent oxygen detoxification pathway, including NADH oxidase, rubredoxin, thioredoxin reductase, thioredoxin, and the C subunit of an alkyl hydroperoxide reductase [3], then having all the activities required for the complete reduction of superoxide. Testing this scheme of dioxygen detoxification will require a multidisciplinary approach but, ultimately, comparative functional analysis of these pathways in vivo and in vitro may reveal a relationship between Tp oxidative stress response and syphilis pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been shown that Dv superoxide reductase can be the final electron acceptor of a NADPH/NADPH oxidoreductase/rubredoxin electron transfer chain in vitro [20,21]. In Tp, analysis of the full genome shows the presence of homologues for the additional constituents of a primitive SOR-dependent oxygen detoxification pathway, including NADH oxidase, rubredoxin, thioredoxin reductase, thioredoxin, and the C subunit of an alkyl hydroperoxide reductase [3], then having all the activities required for the complete reduction of superoxide. Testing this scheme of dioxygen detoxification will require a multidisciplinary approach but, ultimately, comparative functional analysis of these pathways in vivo and in vitro may reveal a relationship between Tp oxidative stress response and syphilis pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, analysis of the full genome indicates that Tp lacks the classic antioxidant defense enzymes such as superoxide dismutase (SOD), catalase or peroxidases [3]. It was only recently reported that Tp presents an alternative way to survive upon transient exposure to oxygen and a reactive oxygen species (ROS) in the environment, by expressing the gene for a superoxide reductase (TP0823) [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Very few protein homologies between Treponema pallidum and Borrelia burgdorferi were discovered by revelation of the primary sequence of their genomic DNA (Fraser et al, 1997(Fraser et al, , 1998. However, FtsZ, the homologue of tubulin involved in prokaryotic cell division, appears to be universal in eubacteria and archaebacteria (Erickson and Stoffler, 1997).…”
Section: Motility Proteins and The Search For Bacterial Homologuesmentioning
confidence: 99%
“…Although the underlying genetic traits contributing to the differences in disease have not been identified, the release of three Borrelia genome sequences (one from each 21 species) should aid in this endeavor [5,[11][12][13]. These genomes have several common features, including a linear chromosome and a large number of smaller DNA molecules (plasmids), some of which are linear and others circular [14][15][16][17].…”
Section: Genome and Molecular Genetics Of B Burgdorferimentioning
confidence: 99%